Pedagogical proposal for the development of English communicative competence in first grade elementary school students - Arlette Ximena,; Clara Rocío, (Rastros Rostros, 2024)
The acquisition process of learning a foreign language is key to strengthen the bases of education in the Modern School, since it presents a new vision in its educational curriculum, creating technological access, cultural exchanges with other countries, among others, which forces teachers to be trained in all areas of knowledge, especially in Spanish and English.